Classroom Experiences- and their Proyection in Fieldwork Dynamics- in Teacher Training in the Major of Spanish Teaching - Aguirre Chaves, Marlene (2014)
This essay has as its main objective to describe the experiences of the fieldwork and classwork done simultaneously and steadily in the courses for the Bachelor’s Program for Spanish Teaching at “Universidad Nacional,” Costa Rica, which are stressed in the last two courses “DEY458 Desafíos Didácticos en la Práctica Docente” and “LCG400 Seminario de Innovación y Producción Educativa” and which may be described, depending on their conceptualization, as research or outreach projects. Different experiences about the work done are presented by referring to four factors that play a role in this process, the scenarios in which the research projects are located, pedagogical mediation, which is a space for interaction between the elements of the teaching-learning process and the participants involved, teacher training, which plays an active role in any academic activity, and lastly, the modus vivendi as a change factor influenced by the era of information technologies.